2021
DOI: 10.1126/sciadv.abg7261
|View full text |Cite
|
Sign up to set email alerts
|

Ancient genomes reveal long-range influence of the pre-Columbian culture and site of Tiwanaku

Abstract: Tiwanaku civilization flourished in the Lake Titicaca basin between 500 and 1000 CE and at its apogee influenced wide areas across the southern Andes. Despite a considerable amount of archaeological data, little is known about the Tiwanaku population. We analyzed 17 low-coverage genomes from individuals dated between 300 and 1500 CE and demonstrated genetic continuity in the Lake Titicaca basin throughout this period, which indicates that the substantial cultural and political changes in the region were not ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Additional studies have provided evidence that the ancient Rio Uncallane samples also exhibit continuity with later pre-European contact populations within the region. 75 We performed principal components analysis, generated maximum likelihood trees, and examined population substructure via cluster analysis using samples from the Human Genome Diversity Project (HGDP), Simons Genome Diversity Project (SGDP), and ancient DNA datasets from the Americas (Figure 2; Supplementary Table S2). [79][80][81][82][83][84][85][86][87] Our cluster analysis revealed that the 25 contemporary Peruvians from Lima (PEL) from the 1000 Genomes Project 77 and 5 ancient individuals from Rio Uncallane 76 exhibit over 95% estimated Indigenous American ancestry (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have provided evidence that the ancient Rio Uncallane samples also exhibit continuity with later pre-European contact populations within the region. 75 We performed principal components analysis, generated maximum likelihood trees, and examined population substructure via cluster analysis using samples from the Human Genome Diversity Project (HGDP), Simons Genome Diversity Project (SGDP), and ancient DNA datasets from the Americas (Figure 2; Supplementary Table S2). [79][80][81][82][83][84][85][86][87] Our cluster analysis revealed that the 25 contemporary Peruvians from Lima (PEL) from the 1000 Genomes Project 77 and 5 ancient individuals from Rio Uncallane 76 exhibit over 95% estimated Indigenous American ancestry (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Tiwanaku covered over 40 hectares and harbored tens of thousands of inhabitants with monumental religious architecture, metal technology, chicha beer brewing, specialized craft production, and new strategies for agricultural intensification. 64,74 The city harbored diverse groups from distant regions such as the Amazon 75 and lay at the heart of expansive cultural phenomena that incorporated proto-urban centers and agricultural villages over some 12.5 million km 2 . Around 1.5 ka (500 CE), the Tiwanaku empire faded, giving way to the Late Intermediate Period, 0.9-0.5 ka (1000-1450 CE).…”
Section: Cooperation and Socioeconomic Change In The Ancient Andean H...mentioning
confidence: 99%
“…All samples from the Americas pre‐date 16th‐century European contact (see Table S2 for sample metadata). In our analyses, we use a comparative data set of 115 shotgun data samples and 428 legacy 1240k samples (Bergström et al, 2020; Bongers et al, 2020; de la Fuente et al, 2018; González‐Fortes et al, 2019; Günther et al, 2015; Lindo et al, 2018; Lipson et al, 2017; Mallick et al, 2016; Martiniano et al, 2017; Mathieson et al, 2015; Moreno‐Mayar et al, 2018; Nakatsuka, Lazaridis, et al, 2020; Nakatsuka, Luisi, et al, 2020; Olalde et al, 2018, 2019; Popović et al, 2021; Posth et al, 2018; Prüfer et al, 2014; Raghavan et al, 2015; Salazar et al, 2023; Valdiosera et al, 2018; Villalba‐Mouco et al, 2019). A complete list of the comparative samples used in this study and relevant citations are provided in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of pre-Hispanic and modern-day genomic diversity indicate that the regional genetic substructure in the Central Andes and adjacent geographic regions has persisted for at least 2000 years (30)(31)(32)(33)(34). This allows for the identification of genomic ancestries that are associated with larger geographic regions during that time span [e.g., NorthPeruCoast, SouthPeruHighland, and TiticacaBasin following the nomenclature by Nakatsuka et al (34)] (Fig.…”
Section: Ancestry and Genetic Population Structure In The Urubamba Va...mentioning
confidence: 99%